Waste to power: Experimental investigation and prediction of fuel injection pressure effect on the outputs of DI-CI engine fed by ternary blends using artificial intelligence - Rajak, Upendra; Panchal, Manoj; Prasanna, P. Lakshmi; Nagasai, Chinthala; Agbulut, Umit (SPRINGER, 2025)
Fossil fuels and the tangible outcomes resulting from their massive use are among the most important problems of today. Researchers have been making intense efforts for a long time to reduce the damage caused by fossil fuel use. The transportation sector is one of the sectors where fossil fuels are used intensively. Instead of using fossil fuels in internal combustion engines, the seeking for more environmentally friendly renewable or alternative fuel has continued. In this framework, the present research involves experiments and predictions with waste plastic oil (WP) and ethanol (E) with diesel (D100) in a direct injection (DI) compression ignition engine at varying fuel injection pressure (FIP). The tangibles of the experimental evaluation involve the transformation of waste plastic into oil, known as waste plastics oil, and examining its operational, combustion, and emission specifics. The incorporation of E alcohol in the blend resulted in slight fluctuations in both brake thermal efficiency (BTE) and brake-specific fuel consumption (BSFC). Simultaneously, the highest achieved BTE value of 30.8% was observed for the fuel blend E10WP10D80, consisting of 10% E, 10% WP, and 80% D100 fuel at maximum load conditions with 600 bar FIP. Additionally, a reduced BSFC value of 286.2 g kWh-1 was obtained for the same blend at 600 bars of FIP. The discharge parameters of E10WP10D80 at 12 Nm were as follows: Carbon monoxide (CO) discharges was 0.05%, hydrocarbon (HC) discharges were 17 ppm, carbon dioxide (CO2) discharges were 4.7%, oxide of nitrogen (NOx) discharges were 829 ppm, and smoke discharges were 7.2%. Furthermore, the results predicted a satisfied R-value of greater than 0.9 for all outputs. Finally, it is seen that an increment in FIP helps to improve engine performance, while more NOx and smoke outputs for the tested blends.
Keywords: Alternative fuel; Ternary blends; Waste plastics oil; Artificial Intelligence; Engine behavior; DIESEL; COMBUSTION; METHANOL; EMISSIONS; BIODIESEL; AMMONIA; RATIO; Thermodynamics; Chemistry